The Role of Collaborative Learning in Enhancing Creativity in Visual Arts Education - Gadoyev Ibrohim Niyozovich (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This article examines the role of collaborative learning in enhancing creativity in visual arts education. It explores pedagogical strategies such as group projects, peer feedback, and interactive discussions that foster students’ artistic competencies, problem-solving skills, and creative thinking. The study highlights how collaborative approaches encourage engagement, independent thought, and innovation in students’ artistic practices.